Update on the Dispersal of Aedes albopictus in Mexico: 1988–2021 - Ortega-Morales, Aldo I.; Pérez-Rentería, Cresencio; Ordóñez-Álvarez, José; Salazar, Juan Adrián; Dzul-Manzanilla, Felipe; Correa-Morales, Fabián; Huerta-Jiménez, Herón (Frontiers in Tropical Diseases, 2022)
The Asian tiger mosquito Aedes albopictus (Skuse) is one of the most important mosquito species in public health due to the variety of disease-causing viruses that this species can transmit. In Mexico, Ae. albopictus was reported for the first time in 1990 in the state of Tamaulipas, bordering to the state of Texas (USA). Since then, Ae. albopictus has been reported in 15 Mexican states. Currently, this species is present in all tropical and subtropical regions of the country and its presence is common in the states of the Gulf of Mexico and Chiapas. In the present study, the presence of Ae. albopictus is reported in six additional states: Colima, Guanajuato, Jalisco, Puebla, Oaxaca, and Querétaro. The rapid dispersal of Ae. albopictus in Mexico represents a risk to public health, and the surveillance of this species in regions where it has not yet been reported is essential as part of Mexican entomological surveillance programs.